Parameters of Proper Marketing Strategy of Selected Home Appliances in Kolkata - Ghosh, Chinmoy (International Research Journal of Management, IT & Social Sciences, 2016)
Marketing strategies always chalk out in a specific manner, depending on that the companies can achieve their goal. This paper examined that the combination of five parameters (quality of material, brand, referral system, communication, niche market) create structured marketing strategy, which will generate us a new model.